Knowledge management practices in the public sector - Ismyrlis, Vasileios, 1971-; Tarnanidis, Theodore; Moschidis, Efstratios (Advances in knowledge acquisition, transfer, and management (AKATM) book series., 2020)
"This book explores paradigms of knowledge management implantation in the public sector"--Provided by publisher"--